Cadangan bagi membangunkan sistem pengangkutan ringan halaju rendah jenis "articulating" bagi kegunaan membawa pelawat di UTM - Abdul Aziz, Azhar (Faculty of Mechanical Engineering, 2004)
Chassis and suspension system play an important role in the performance of a vehicle when it comes to safety and passenger comfort. The objectives of this project are to develop a â€œhop-in and hop-outâ€? recreational vehicle with a capacity of eight-passenger, fitted with a dual-fuel system and to analyse the performance of its chassis and suspension system. This showcase vehicle is manufactured by a team of engineers from the Automotive Development Centre (ADC) in UTM. Both the chassis and suspension analyses are rigorously performed using industrial-standard computer software. The safety factor requirement for the vehicle chassis is set for over a factor of 2.0 and its torsional stiffness must in the range from 3000Nm/degree to 9000Nm/degree. The vehicle chassis is analyzed in several conditions, namely static, bumping and braking, while the comfort performance is largely speculated to depend on the demand of user. In this project, the comfortable performance for tramcar which is the performance of its suspension system is benchmarked with that of the performance for Proton Waja 1.6. The level of comfort for the tramcar suspension system is referred to the performance results with particular emphasis on bouncing, pitching and rolling. From the results of the analyses the tramcar has achieved satisfactory performance criteria. The safety factor is over the minimum requirement for a typical utility vehicle and the torsional stiffness is within the allowable range. In addition the suspension system shows the results are comparable to the performance of the Proton Waja 1.6.